Comparison of Thiamine Contain in Mung Beans (Vigna radiata L.) and Soybean (Glycine max (L.) Mer.) with Fresh and Boiled Treatment - Agus Suprijono; Yuni Utami (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2020)
Mung beans (Vigna radiata L.) and soybeans (Glycine max (L.) Mer.) are species of nuts that contain good nutrients for health, such as thiamine or vitamin B1. Thiamine can increase appetite and important in nervous system. Both species of beans can be processed into consumable sprouts, both fresh and boiled. The research aims to compare the concentrations of thiamine in mung beans sprouts and soybeans sprouts in fresh and boiled conditions. The research procedure began with prepared fresh and boiled samples. Boiled samples were prepared by boiled sprouts for 3 minutes at 100°C. Thiamine was extracted from samples used 0,1 N HCl by heated on a water bath at 100°C for 30 minutes. The extracts of fresh and boiled sprouts were analyzed qualitatively used chemical reagents and quantitatively used spectrophotometer UV-Vis. Qualitative analysis showed that both fresh and boiled mung beans sprouts and soybeans sprouts contain thiamine. Quantitative test results for boiled and fresh mung beans sprouts were 0,26% and 0,15%, while soybeans were 0,64% and 0,44%, respectively. The thiamine content in soybeans sprouts is higher than in mung beans sprouts. Decrease of thiamine concentration in mung beans sprouts was higher at 42,31%, for boiled sample than soybeansbenas sprouts at 31,25%. The results of statistical tests used the t test showed a significant difference in thiamine concentration between fresh and boiled beans, both mung beans and soybeans.